Letters from F. X. Martin to Florence O'Donoghue regarding arrangements for O'Donoghue’s 1966 Thomas Davis lecture ‘Ceannt, O'Rahilly and the Military Plan’ and publication of series in Irish Historical Studies, - Martin, F. X. (Francis X.) (1965)
Includes list of lectures in 1966 Thomas Davis lecture series 'The Easter Rising - How and why did it happen', letter from Agnes McCullough regarding ‬D‬enis McCullough's recollections and list of members of Irish Republican Brotherhood Supreme Council.